Information Technology Governance Model: Design for a Faculty of Engineering of a Peruvian Public University - Malca Chuquiruna, Raquel Beatriz (2022)
The purpose of the study was to propose an information technology governance model based on COBIT 2019 for a faculty at a peruvian public university aligned to the strategic plan of said faculty and university. The population consisted of 89 people from the various offices of the public university (management staff, planning area, internal control, legal area, operations area, human resources area, and IT area) and a faculty of engineering (administrative staff, teaching staff, managerial staff, and informatics unit). The proposed model included indicators such as: number of processes by level of maturity, number of information technology goals aligned with institutional goals, percentage of progress in the implementation of COBIT domains and processes in the university, and percentage of available information technologies for COBIT implementation. The implementation of this model will allow the faculties or professional schools of informatics and systems engineering to improve their management, contributing to the factors of strategic alignment of information technologies. It is recommended to implement this model in systems engineering faculties or professional schools of public or private universities, with similar organizational structures.